Case report: XMEN disease: a patient with recurrent Hodgkin lymphoma and immune thrombocytopenia - de Groot, Pieter F.; Kwakernaak, Arjan J.; van Leeuwen, Ester M. M.; van Spaendonk, Rosalina M. L.; Kooi, Evert-Jan; de Jong, Daphne; Kuijpers, Taco W.; Zijlstra, Josée M.; de Bree, Godelieve J. (Frontiers in Medicine, 2023)
Here we present the case of a 28-year-old man with X-linked immunodeficiency with magnesium defect, Epstein–Barr virus (EBV) infection and neoplasia (XMEN) disease. He presented with immune thrombocytopenia within 1 year after successful autologous hematopoietic stem cell transplantation for recurrent EBV-associated classical Hodgkin lymphoma (CHL). The combination of EBV- associated malignancy, autoimmunity, recurrent airway infections at young age and bronchiectasis, prompted immunological investigation for an inborn error of immunity (IEI). Genetic testing revealed XMEN disease. XMEN disease is characterized by a glycosylation defect due to mutations in the MAGT1 gene. Germline mutations in the MAGT1 gene disrupt glycosylation of the NKG2D receptor in immune cells, including natural killer and CD8-positive T cells, vital for immune surveillance, especially against EBV. Consequently, individuals with XMEN disease, are prone to EBV-associated lymphoproliferative disorders in addition to auto-immunity. Early recognition of adult onset IEI-related B-lymphoproliferative disorders, including CHL is of vital importance for treatment decisions, including (allogeneic) haematopoietic stem cell transplantation and family screening.